Dampak Pengelolaan Kelas yang Efektif bagi Keberhasilan Kegiatan Belajar-Mengajar Guru Pendidikan Agama Kristen Masa Kini - Ramses Simanjuntak (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
Teachers have an enormous share of the success of learning in school. Teachers play a role helping the development of learners to achieve their goals optimally. In the classroom teachers carry out two main activities namely teaching and learning activities and management of the class.Classroom management is not just a classroom setting, physical facilities and routines, but also managing the various things covered in the learning component. Classroom management activities are intended to create and maintain a conducive classroom atmosphere. So that the process of teaching and learning can take effectively and efficiently. Effective means achieving goals in accordance the precisely designed of plan. Efesin is the achievement of learning objectivesas planned more quickly.